Nanocomposite hydrogels based on nanocellulose for applications in agriculture - Nascimento, Diego Magalhães do (2019)
NASCIMENTO, Diego Magalhães do. Nanocomposite hydrogels based on nanocellulose for applications in agriculture. 2019. 163 f. Tese (Doutorado em Química) - Universidade Federal do Ceará, Fortaleza, 2019.